A Study about Micro-Bad News in Haematooncological hospitalized patients. The daily medical communication - Cruzado, Juan Antonio; Barbero, Javier; Díaz-Sayas, Laura (Psicooncología, 2010)
Literature has shown that accumulated daily hassles can also impact as life events do. In Psychooncology, studies have mainly focused on impact generated by breaking Bad News at isolated moments. During the disease process, patients do not only receive bad news related to diagnosis, non-effective treatments or bad prognosis but also another daily comments which can affect them negatively. This kind of messages have been named Micro-Bad News (MBN). The present study tries to explore the main characteristics of this daily source of stress for inpatients. After analysing 500 MBN, results show that more than half of the sample (N = 296) receive at least one MBN during the hospital admission. MBN are usually known but unexpected at that moment. MBN´s content is related to information about the patient´s privated sphere (as changes in the space/time expectations) and the posibility of suffer fisical damage (mainly by diagnosis tests experienced as unpleasant by the patient). Finally, some recomendations are proposed in the base of the results to achive an quality integrative assisstance for inpatients.
Keywords: Doctor-patient communication; Micro-stressors; Hassles; Micro-Bad News